Grignard reagents and transition metal catalysts : formation of C-C bonds by cross-coupling - Cossy, Janine (De Gruyter, 2016)
In 1912, the Chemistry Nobel Prize was awarded for the discovery of the so-called Grignard reagents. Nowadays, many transition metal variants are developed to modify reactivity and selectivity of the C-C bond formation reaction. The Grignard reaction is one of the fundamental organometallic reactions, often used in alcohol syntheses. With transition metals like iron, cobalt and nickel or with noble metals like copper, silver and palladium, modern Grignard reagents can be designed in reactivity, selectivity and functional group tolerance. This book, written by international experts, presents an overview on timely Grignard chemistry involving transition metals.